Factors affecting employee performance in religious courts - Cahaya, Yohanes Ferry; Wita, Nurul Kurnia; Sunarto, Sunarto; Suharyanto, Suharyanto; Hidayat, R. Taufik (Enrichment : Journal of Management, 2024)
This study investigates the factors influencing employee performance at the Religious Court of Unaaha, Class IB, in Konawe Regency, Southeast Sulawesi Province, Indonesia. Using the multiple linear regression analysis method to test hypotheses, these variables were evaluated based on feedback from 30 employees. Findings indicate that while compensation and motivation are at satisfactory levels, neither significantly influences employee performance. However, a conducive work environment has been shown to have a positive and significant impact on employee performance. The implication of these findings underscores the need for greater attention to the work environment factor to enhance employee performance. Awareness of the importance of a favorable work environment can help organizations foster a more productive and motivating atmosphere for employees. Recommendations resulting from this study include evaluating compensation policies, enhancing motivation through career development, and paying closer attention to the work environment. These recommendations can assist the Religious Court of Unaaha in improving employee performance and overall organizational effectiveness